Classification of land use and occupation in urban streams PPA using images from Remotely Piloted Aircraft - Franco, Fernanda Miguel; Chaves, Arthur Guilherme Schirmbeck (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Technologies, increasingly developed, are emerging as a useful tool for evaluating changes, as well as supporting proposals aimed at mitigating anthropization. The work aimed to classify the use and occupation of three urban streams in the city of Cáceres-MT, using an Remotely Piloted Aircraft (RPA). The streams Fontes, Sangradouro and Renato were flown over to obtain aerial photographs and later, with the processing of the images, the orthomosaic was obtained. This, in turn, was used to classify land use and occupation within the limits of the Permanent Preservation Area (PPA). With the centimetric spatial precision of the generated orthomoisaic, it was possible to carry out a precise analysis of the local occupation and analyze that the riparian forest area as well as the deposition of effluents along the streams, does not comply with the current Brazilian Forest Code. The use of photogrammetry equipment, more specifically the RPA, proved to be advantageous due to its agility in collecting data in the field, offering concise results and excellent image quality (orthomosaic), making it possible to carry out predicted assessments of environmental impacts suffered, also providing a database for monitoring the area.
Keywords: Permanent preservation area; Urban river; Remotely Piloted Aircraft